Evaluation of Neurovascular Coupling Behaviors for FES-Induced Wrist Movements Based on Synchronized EEG-fNIRS Signals - Mao, He; Meng, Haotian; Tan, Qiyun; Williams Samuel, Oluwarotimi; Li, Guanglin; Fang, Peng (IEEE transactions on neural systems and rehabilitation engineering, 2025)
The neuronal activities and cerebral hemodynamic responses are closely linked via the neurovascular coupling (NC) mechanism. This mechanism is strongly associated with the brain state and alters with the pathological conditions such as motor dysfunctions. Clinically, functional electrical stimulation (FES) is being increasingly used for motor function restoration, but the impact of FES on NC behaviors is still lack of study, which would prevent the understanding of FES in improving neurorehabilitation performance. In this work, we studied the NC behaviors based on synchronously recorded electroencephalography and functional near-infrared spectroscopy (EEG-fNIRS) signals during FES-induced wrist movements from twenty healthy subjects. Oxygenated (HbO) and deoxygenated (HbR) hemoglobin concentrations were computed from the fNIRS signals, event-related (de-)synchronization (ERD/ERS) was computed from the EEG in alpha and beta bands, and transfer entropy (TE) was used to assess the coupling between the two signals. Experimental results revealed that the NC behavior of FES-induced movements was similar to that of voluntary movements, with a slower HbO activation process but longer duration. A bidirectional coupling relationship was observed between EEG power envelope and HbO time series but the TE from HbO to EEG (TE {}_{HbO→ EEG} ) was larger than that for the opposite direction. Significant differences were found between the FES-induced and voluntary tasks, where the former showed higher TE {}_{HbO→ EEG} on the ipsilateral sensorimotor cortex than the latter, which indicates that FES could improve the regulatory effect of ipsilateral cerebral blood flow on neuronal activities. This work may contribute to understanding the neurorehabilitation mechanism by FES and provide evidence-based support for clinical application from the perspective of NC.